Hak Untuk Dilupakan: Penghapusan Jejak Digital Sebagai Perlindungan Selebriti Anak dari Bahaya Deepfake - Muhammad Deckri Algamar; Aliya Ilysia Irfana Ampri (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
Child celebrities coming from Youtube, TikTok, and other social media are at high risk of being exploited and sexualized over their content. As Youtuber parents nonchalantly record their children without worries about exposing their privacy to the internet, predators lurk while seeking to exploit the minors at any moment’s notice. The loss of privacy experienced by child celebrities may contribute to the loss of self-ownership, even leading to cases of depersonalization where children become unable to separate their authentic identity from their celebrity persona. Furthermore, another concerning issue on disseminating child sexual abuse materials depicting child celebrities further threatening minors on the internet. Where regulations have been put in place to protect children in conventional manners, it is being challenged when facing the new Deepfake technology that can create artificially generated pornographic content using the child’s face. Through literary review over materials related to child celebrity’s privacy and the rampant use of Deepfake. This paper proposed that a crossover between Pornography Law, ITE Law, and Child Protection Law is required in adapting to these unconventional circumstances. Specifically, this paper explores the option to utilize “Hak Untuk Dilupakan” as stipulated under Article 26 of UU ITE to protect children’s privacy and prevent certain content from being further disseminated, either by delisting or through a take-down mechanism under court orders.